The flexible workplace: What have we learned? - Rodgers, Charles S. (Human Resource Management, 1992)
AbstractData collected on white‐collar and services sector jobs in over 20 large corporations show both the enormous demand from employees for more flexibility in the workplace and the considerable resistance to it by supervisors. The interest in more flexible work practices stems from the tremendous time constraints faced by the many employees with significant family responsibilities. Current practices, schedules, and management philosophy are no longer adequate for workers in this important segment of the labor force and impede them from being as productive as they could be. The major barriers and enablers to flexibility are discussed, and the data on benefits are reviewed. It is argued that if progress toward a more flexible workplace is to continue, the emphasis will have to shift from a strategy of accommodating valued employees to new ways to manage and organize how work is done. © 1993 by John Wiley & Sons, Inc.